Gamma Heating Evaluation of Silicide RSG-GAS Multipurpose Reactor. Issue 1 (1st August 2022) - Rohanda, A; Waris, A; Kurniadi, R; Bakhri, S
Abstract: In research reactor, gamma heating deposited in the samples is an important issue because it is related to the samples and the reactor operational safety. Multi Purpose Reactor (MPR) 30 MWth or its called Reaktor Serba Guna G.A. Siwabessy (RSG-GAS) is a research reactor that play a role as a place to irradiate various target material type. RSG-GAS has been operating since 1987 and the last measurement of gamma heating in the core was conducted around twenty years ago in oxide core. In 1996, RSG-GAS core was converted from oxide fuel type to silicide fuel type. The purpose of the conversion are to improve the performance and efficiency of RSG-GAS. As part of RSG-GAS irradiation facilities safety analysis, the gamma heating measurement was re-conducted in order to obtain latest data as benchmark data in silicide core. This paper presents the results of gamma heating measurement of LEU silicide RSG-GAS core in Central Irradiation Position (CIP) at 15 MW and 30 MW power level using gamma calorimeter. There were four types of calorimeter used, which were calorimeter with graphite (C) sample, iron (Fe) sample, aluminum (Al) sample and zirconium (Zr) sample. Gamma heating calculations using GAMSET code were performed to verify the measurement results. The measurement results are lower than the GAMSET results and the gamma heating value increases in proportion to the increase of calorimeter sample atomic number. This results are corresponds to gamma heating benchmarking results of RSG-GAS oxide core. Several optimization efforts both measuring and modeling with GAMSET were conducted as an evaluation and justification of the results. The best optimization results are achieved using the maximum value of the measurement and adjusting the power peaking factor (PPF) distribution. The calculated gamma heating value optimization results at 15 MW power are 2.78 W/g (C sample), 2.74 W/g (Al sample), 3.36 W/g (Fe sample) and 4.60 W/g (Zr sample) while at 30 MW power level are 5.57 W/g (C sample), 5.49 W/g (Al sample), 6.75 W/g (Fe sample) and 9.23 W/g (Zr sample). The best optimization results serve as a benchmark data for developing new gamma heating calculation programs based on 18 gamma energy groups.